Geostationary electron dynamics: ICARE_NG2 observations and new analytical model of daily electron fluxes driven by solar wind conditions - Caron Pablo; Bourdarie Sébastien; Carron Jérôme; Ecoffet Robert; Terzo Sergio; Panitzek Kamill; Heil Melanie (Journal of Space Weather and Space Climate)
The effects of the space radiation on spacecraft materials and devices are significant design considerations for space missions. In order to meet these challenges, the radiation environment must be understood. Measuring energetic particles in the radiation belts is therefore crucial, and this is why ICARE (Influence sur les Composants Avancés des Radiations de l’Espace) radiation monitors have been developed over several decades. Two ICARE_NG2 (for the second version of the New Generation of the instrument) radiation monitors have recently been launched on HotBird 13F and 13G satellites at the end of 2022, reaching the geostationary orbit in 2023 and providing measurements of electrons of the outer belt. The methods used to derive these electron fluxes are detailed and the results compared with NGRM (Next Generation Radiation Monitor) and specification models. The observed electron dynamics are strongly correlated with solar wind data, and a fully analytical model is developed. This model provides an accurate representation of the measurements, using a limited number of parameters.